Vaccinium carmesinum (Ericaceae), a new species of blueberry from Mt. Tago Range, Mindanao Island, Philippines - Tamayo, Maverick N.; Coritico, Fulgent P.; Amoroso, Victor B.; Penneys, Darin S.; Tandang, Danilo N.; Fritsch, Peter W. (Phytotaxa, 2022)
Vaccinium carmesinum is described as a new species of Ericaceae from Mt. Tago Range, Mindanao Island, Philippines. It is similar to V. platyphyllum Merrill and V. luzoniense S.Vidal but is distinct from the former by longer and wider leaves, longer racemes, longer bracts, glabrous corollas, and glabrescent fruits, and from the latter by longer petioles, leaf glands distributed along the blade margin, glabrous rachis, and lanate filaments. Vaccinium carmesinum bears the widest leaves among Philippine Vaccinium. Its discovery increases the number of Vaccinium species recognized in the Philippines to 37.